2020
DOI: 10.1186/s41927-020-00134-7
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and early rheumatoid arthritis

Abstract: Background: Previous studies have linked rheumatoid arthritis (RA) risk and disease activity with vitamin D-deficiency (low serum 25-hydroxyvitamin D (25OHD)), but a causal role for vitamin D in RA is still unclear, with conflicting results from many previous studies, partly due to heterogeneity in study design and patient populations. In this study we aimed to (1) analyse serum 25OHD in early inflammatory arthritis, (2) compare 25OHD with disease activity and fatigue in early RA and (3) determine whether low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…Previously completed studies suggesting a correlation between early RA and Vitamin D deficiency were reexamined using data from the Birmingham Early Arthritis Clinic Cohort (BEACON) ( 152 ). Using samples from 790 patients enrolled in the cohort, the authors, including Karim Raza and Andrew Filer, the primary investigators of the BEACON cohort, found no clear relationships between early RA and 25OHD, or low serum 25-ydroxyvitamin D) ( 152 ). By using synovial fluid, Raza and his team recognized that the make-up of joint fluid in early RA patients was distinct from that of other inflammatory diseases ( 153 ).…”
Section: Prospective Cohort Studies Among Those With Symptoms or Undi...mentioning
confidence: 99%
“…Previously completed studies suggesting a correlation between early RA and Vitamin D deficiency were reexamined using data from the Birmingham Early Arthritis Clinic Cohort (BEACON) ( 152 ). Using samples from 790 patients enrolled in the cohort, the authors, including Karim Raza and Andrew Filer, the primary investigators of the BEACON cohort, found no clear relationships between early RA and 25OHD, or low serum 25-ydroxyvitamin D) ( 152 ). By using synovial fluid, Raza and his team recognized that the make-up of joint fluid in early RA patients was distinct from that of other inflammatory diseases ( 153 ).…”
Section: Prospective Cohort Studies Among Those With Symptoms or Undi...mentioning
confidence: 99%
“…It may result in joint destruction, loss of function, and disability and can negatively influence cardiovascular health [10]. It has recently been found that 25-OH-D level is associated with disease progression and neuropathic pain in RA patients [5,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…1) Several recent studies have shown that vitamin D deficiency is associated with some types of cancers [2][3][4] as well as chronic diseases such as hypertension, 5) diabetes, 6) cardiovascular diseases, 7) and autoimmune diseases. 8) In meta-analysis of retrospective studies, higher serum vitamin D levels were associated with lower risk of colorectal and breast cancer. 3,4) A meta-analysis of nine prospective cohort studies also showed that increase in vitamin D intake and serum 25-hydroxycholecalciferol (25(OH)D) levels reduced the risk of colorectal cancer incidence.…”
Section: Introductionmentioning
confidence: 99%